The evolution of performance metrics in the competitive arena of freestyle wrestling olympic finalists - Latyshev S.V. , (Theory and Practice of Physical Culture, 2025)
Objective of the study was to examine the evolution of performance metrics for wrestlers in the discipline of freestyle wrestling at the Olympic Games, both before and after the rule modifications implemented in 2013. Methods and structure of the study. The following methods were used in the work: analysis of scientific and methodological literature, video analysis and timing of competitive duels for first and third places in each weight category at the Olympic Games in Paris (2024) in men's wrestling (discipline – freestyle wrestling), methods of mathematical statistics. Results and conclusions. In the research, we calculated specific metrics for the performance of the finalists in the wrestling competition at the Beijing Olympics (2024). These metrics included the average duration of each bout, the average time spent in the standing and clinching positions, activity, effectiveness, the number of high-scoring moves, and the reliability of the wrestler's offensive and defensive strategies. We then compared these findings with the results of our previous studies, which analyzed the performance of wrestlers at the Olympic Games in Atlanta (1996) and Sydney (2000). A comparative study revealed that the alterations in the rules governing competition in 2013 had a substantial effect on the performance of competitive activities, resulting in a shift towards enhancing the entertainment value of competitive matches. Specifically, the average duration of fights decreased due to an increase in the number of early victories. The intensity and overall effectiveness of the fights increased approximately twofold. The reliability of offensive actions decreased, while defensive actions increased. The proportion of high-scoring TTA remained relatively stable.